Survival and Replication of Zika Virus in Diapause Eggs of Aedes Albopictus From Beijing, China - Zhang, Qianghui; Jiang, Yuting; Li, Chaojie; Gao, Jian; Zhao, Teng; Zhang, Hengduan; Li, Chunxiao; Xing, Dan; Dong, Yande; Zhao, Tongyan; Guo, Xiaoxia (Frontiers in Microbiology, 2022)
Zika virus (ZIKV) has emerged as a globally important arbovirus. The virus is primarily transmitted to humans through the bite of an infective Aedes albopictus in temperate area. Vertical transmission of Zika virus by Ae. albopictus is determined and has been suggested to be a means by which the virus could persist in nature. Ae. albopictus undergoes a well characterized photoperiodic diapause. Viruses are harbored by overwintering mosquitoes in diapause contribute to the resurgence of vertebrate diseases in the following spring, yet little is known about the impact of diapause on regulation of viral replication and survival. The purpose of the current study is to determine that Ae. albopictus in Beijing are highly susceptible to ZIKV (92.3%), and viable virus is passed to their organs of progeny via vertical transmission. Moreover, diapause eggs (Diapause incidence 97.8%) had significantly lower minimum infection rates and filial infection rates of the first gonotrophic cycle than those of the second gonotrophic cycle in the short-day photoperiod group; As the development of diapause eggs, the minimum infection rates and ZIKV RNA copy number increased significantly, suggesting virus RNA replication occurred in the diapause eggs. Meanwhile, eggs from the ZIKV-infected mosquitoes had a significantly lower hatching rate compared with uninfected mosquitoes, implying an intriguing interaction between diapause eggs and virus. The findings here suggest that vertical transmission of ZIKV from diapause eggs to progeny may have a critical epidemiological role in the dissemination and maintenance of ZIKV circulating in the vector.